The multifaceted impact of US trade policy on financial markets - Boer, Lukas,Menkhoff, Lukas,Rieth, Malte (DIW Berlin, German Institute for Economic Research, 2021)
We study the multifaceted effects and persistence of trade policy shocks on financial markets in a structural vector autoregression. The model is identified via event day heteroskedasticity. We find that restrictive US trade policy shocks affect US and international stock prices heterogeneously, but generally negatively, increasing market uncertainty, lowering interest rates, and leading to an appreciation of the US-Dollar. The effects are significant for several weeks or quarters. Regarding shock types, we reveal a dominating trade policy uncertainty shock and a weaker level shock. Chinese trade policy shocks against the US further hurt US stocks.
urn:nbn:de:101:1-2021081004463431046602
Keywords: Graue Literatur; Außenwirtschaftspolitik; Aktienmarkt; Wechselkurs; Zins; Wirkungsanalyse; VAR-Modell; USA; China; Trade policy shock; structural VAR; stock prices; exchange rates; interest rates; heteroskedasticity